Implementation of an Integrated Approach in Budget Planning for Resource Optimization in Organization - Galuh Prabowo; Lely Ana Ferawati Ekanigsih (Universitas Negeri Semarang, 2025)
This study aims to explore the application of an integrated approach in budget planning to optimize educational resources in the Muadalah Wustho Blokagung Banyuwangi Education Unit. With this approach, the research seeks to improve the efficiency of fund allocation, stakeholder involvement, and transparency and accountability of financial management. This research uses a qualitative approach with a case study method to deeply understand budget planning and management of educational resources in the Muadalah Wustho Education Unit. Data were collected through in-depth interviews, participatory observation and document analysis to gain comprehensive perspectives from various stakeholders. Data analysis was conducted descriptively, researchers identified patterns and developed practical recommendations relevant to the optimization of budget management in this educational institution. The results of this study indicate that an integrated approach to budget planning in the Muadalah Wustho Education Unit is effective in achieving efficient, adaptive and appropriate fund management. This approach is supported by transparency, accountability, and the utilization of technology that enables real-time budget monitoring, thereby increasing stakeholder trust and supporting better quality education.